Effect of Delay due to U-Turn on Pangeran Antasari Road (Case Study U-Turn Near Ganesha Operation) - Dwiana, Yovi; Putra, Sasana; Sulistyorini, Rahayu (Universitas Lampung, 2020)
Pangeran Antasari road is an urban road with 2-ways 4-lanes type (using median). In this median was found U-turn facility near of Ganesha Operation. Based on preliminary observations at the study location (Pangeran Antasari Road), it was seen there vehicles that could’t make a smooth U-Turn movement and other vehicles that were obstructed when passing through this facility, especially during peak hours when traffic volume was high.The objevtives of this study is to know the effect of U-Turn on delays in Pangeran Antasari road, which is near of Ganesha Operation. The method used is Gap Acceptance. It was to determine the value of vehicle travel time that is affected by U-Turn movement vehicles, namely the gap time and follow-up time.Based on the data analysis carried out at the U-Turn near of Ganesha Operation, it can be concluded that the effect of delay is due to the average time of gap accepted and follow-up time. The average time value of gap accepted was 3.64 seconds and 4.35 seconds in the morning and 9.59 seconds and 8.78 seconds in the afternoon. The average follow-up time of the vehicle is 12.72 seconds to 18.2 seconds in the morning and 14.01 seconds to 17.87 seconds in the afternoon.